Controllable Ni-doping and conformal NiO coating of porous flower-like VO2 clusters for high-performance symmetric supercapacitors - Mingxing Zhang; Huang Zhang; Yu Li; Fan Wang; Huihua Li; Jiawei Zhang; Minghua Chen (Next Energy)
With the growing demand for high-performance energy storage devices, vanadium dioxide (VO2) has been emerged as a promising electrode material for supercapacitors due to its unique physicochemical properties and abundant resources. However, the intercalation-pseudocapacitive mechanism and solubility in aqueous electrolytes present challenges to achieving high specific capacitance and cycling stability. This study demonstrates a synergetic modification strategy by introducing nickel dopants and a protective NiO layer to enhance the performance of VO2 electrode materials via a solvothermal method combined with atomic layer deposition (ALD) technology. The synergistic effect of nickel doping ratio and NiO layer thickness on electrochemical performance is systematically investigated. Results show that nickel doping significantly improves the conductivity and activates additional electrochemical sites, enhancing both rate capability and specific capacitance. The conformal NiO layer coating effectively mitigates the VO2 dissolution, leading to improved cycling stability. A quasi-solid-state symmetric supercapacitor using the optimized Ni-VO2@NiO200 composite electrodes delivers a maximum energy density of 4.03 Wh kg−1 and maintains 72.8% capacitance retention after 2500 cycles, significantly outperforming pristine VO2. These findings demonstrate the feasibility of VO2 with structural modification as a high-performance electrode material for supercapacitors, offering valuable insights for future material design in electrochemical energy storage applications.